An assessment of the efficiency of Spanish schools: evaluating the influence of the geographical, managerial, and socioeconomic features. (16th August 2019) - Segovia‐Gonzalez, M.M.; Dominguez, C.; Contreras, I.
Abstract: The aim of the present paper is to explore the efficiency of Spanish schools while simultaneously considering data envelopment analysis (DEA) and multivariate analysis. Test scores from the Program for International Assessment reports are used as outputs while the resources of each institution are considered as inputs to the analysis. The methodology utilized determines the DEA efficiencies under various input/output combinations and the results are interpreted through the application of factor analysis and property‐fitting techniques. The objective of the study is to identify the strengths and weaknesses of each type of school and the connections with the way in which the efficiency is obtained. In the light of the results, the study concludes that there exist differences related with two of the criteria considered: the type of management of the schools and the parental socioeconomic level of the students. However, no differences appear when the geographical location of the institutions is considered to characterize the entities.